Socio-Economic Profile of Muslims in Maharashtra. - Vibhuti Patel (2013)
The Sachar Committee Report (2006) stated that the condition of Muslim in Maharashtra demanded special attention of the state as they constituted the largest religious minority. Seven surveys commissioned by the Maharashtra State Minority Commission discovered that a very large proportion of Muslims live in very dismal economic conditions. This paper collates relevant data from various primary and secondary sources in order to make recommendations for the amelioration of the socio-economic conditions of the Muslim community.